(3MSf GdSeJ aj GdUeJs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hcai gPG LRA dNUJg ef cJGH GdUeJ dCHj HcQ Hf CHj GdOfjG eY RhGFO Ydjg hSejJg CNQL CMeO hGdOGQej hGdJQePj hGHf CHj GdOfjG hGdHjgbj aj TYH GdEjeGf Yf YHO Gddg Hf YeQh Cf QShd Gddg Udi Gddg Ydjg hSde bGd ef UeJ fLGs
(3BNQgG (B:s
(3hbGd BNQ (B: (3egdG oSdjei Cbqdj Gddhe Ch adej (B,, (3ef CbYOJg UQha GdOgQ de jbe (B,,, (3MXj jbUQ Hj Yf cd ecQeI (B,, (3hdG jbUQ Hj Yf fjdgG geej (B,, (3SCdRe GdUeJ eG OGe GdReGf cPG hCefY (B- (3GdOgQ (B- (3ef fWb GddSGf aej hGdMeO ddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\301s
(3cTa GdXfhf (B1\666s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs